KAJIAN INSENTIF PENGOLAHAN KAKAO FERMENTASI UNTUK PETANI DAN KELOMPOK TANI - Satriawan, I Ketut (Agrotekno; Vol 13, No.2 Agustus 2007)
Cocoa  is  a  prospective commodity  export  and  as  a superior commodity of estate crops in Bali. The quality of cocoa is  very  various  and  majority  farmer  processing  it  without fermentation.This  research  aimed  to  determine  minimal  price  of  raw material of wet bean cocoa from the farmer and difference price between  fermented  and  non-fermented  cocoa  as processing incentive which  must  be  give to the  farmer. The research  was done in the farmer group of estate crops of Tabanan Regency.The  processing  unit  of  the  farmer  group  of  estate  crops must  be  buy  a  wet  of  cocoa  bean  from  the  farmer  is  with minimal price Rp. 4.180 per kg. Difference price fermented and non-fermented  cocoa  as  processing  incentive  which  must  be give  to  the  farmer  is  minimal  Rp.  4.590  per  kg,  if  the  price  of non-fermented cocoa is Rp. 11.000 per kg.
Keywords: processing incentive, fermented and non-fermented cocoa